Effectiveness of Using E-Court In Religious Court Proceedings in South Jakarta - Hanif, Hamdan Arief; Wanodyatma, Nike Puspita; Makarim, Faris (Universitas Negeri Medan, 2023)
E-Court is a tool in court that functions as a service to the public in terms of registering cases through online platforms, calculating estimated court costs digitally as well as online payments, online summons and trials. The South Jakarta Religious Court started using the e-court since 2018, when the Supreme Court Regulation (PERMA) No. 3 of 2018 appeared regarding Electronic Administration of Cases in Courts. As time went on, the e-court process began to develop when the Supreme Court Regulation (PERMA) No. 1 of 2019 concerning Administration of Cases and Trials in Courts appeared electronically. The benefits for all parties for e-court users are that all parties will be helped by saving costs and time in the process. The deficiencies that occur are network problems in the e-court application. The type of research used in this writing is qualitative research which produces descriptive analytical data, supported by premier and secondary data sources then data collection techniques by means of observation, interviews and documentation. The results of this study indicate that the process of using e-court in proceedings at the South Jakarta Religious Court includes several stages starting from online case registration, online down-payment of fees, online summons, and online trials. There are several obstacles and opportunities that occur in the process of using e-court in proceedings at the South Jakarta Religious Court. Opportunities that occur are that all parties can benefit more such as saving energy, saving time, and saving costs. The obstacle that occurs is the lack of knowledge for previous advocates regarding existing technology from e-courts at this time. As for its effectiveness in using e-court in proceedings at the Religious Courts, it cannot be said to be fully effective because there are still several obstacles in the process..